THE RELATIONSHIP BETWEEN MINDSET OF PRE-SERVICE ELEMENTARY SCHOOL TEACHER AND ACADEMIC ACHIEVEMENT - Ainur Rosyid (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
This study aimed to examine the relationship between mindset and academic achievement. Data of mindset collected through a survey adopted, adapted, and translated. While data on academic achievement was collected from the study report of students. This research sampled 41 pre-service teachers in their final year. Data were statistically analyzed by using the correlation test of Pearson. The results show that first, growth mindset with some fixed mindset dominated Elementary school pre-service teachers with 82%. Second, pre-service teachers had superb academic achievement. More than half of the academic achievement is categorized into cumlaude. Third, the relationship between mindset and academic achievement is very low / very weak. This means that the mindset does not correlate to the academic achievement of pre-service teachers.